THE ANALYSIS OF E-LEARNING SUCCESS BY USING DELONE AND MCLEAN SUCCESS MODEL (CASE STUDY: PERTAMINA UNIVERSITY) - Burhan Mafazi (Journal of Information Technology and Its Utilization, 2021)
Education is a crucial thing and highly concerned all over the world. As one of the educational institutions, the university has currently applied many information systems because of several obstacles and problems. With the fast development of information and communication technology, the learning process also has improved, known as e-learning. Pertamina University is a private university located in Jakarta, which has six faculties and 15 study programs. Since its inception in 2016, Pertamina University has applied e-learning to its students. Based on the conceptual models developed by DeLone & McLean, this research aims to examine the success of the implementation of the e-learning system in Pertamina University with six variables, which are information quality, system quality, service quality, use, user satisfaction, and net benefit. The results of the study using 610 samples showed that the information quality variable did not affect the user satisfaction variable, which means that the quality of information on e-learning needed to be improved again to get a better response to user satisfaction.